Creation of Corporative Financial Stability Index: Integrated Approach - Lukasevich, I.Y.; Lvova, N.A.; Sukhorukova, D.V. (Journal of Reviews on Global Economics, 2018)
At the present time it is customary to consider the financial stability in the macroeconomic aspect. The existing methodology of its assessment covers mainly the financial market. At the same time, due attention is not paid to companies operating in the real sector of the economy. This paper proposes a methodology for developing indices of financial stability of companies, which allows to take into account both qualitative and quantitative assessment of relevant factors. Its elements and principles of construction are formulated, factors and indicators are defined, as well as methods and approaches to their evaluation. The main directions of its development and application are shown. The proposed approach and the developed methodology can be in demand by representatives of public administration in justifying a wide range of management decisions that require an assessment of financial stability. It may also be of interest to market participants, including relevant institutions, investors and companies attracting investments.